EGFR inhibitors: clinical aspects, risk factors and biomarkers for acneiform eruptions and other mucosal and cutaneous adverse effects - Júlia Kanaan Recuero; Joana Roberta Fitz; Andrea Abe Pereira; Renan Rangel Bonamigo (Sociedade Brasileira de Dermatologia, 2023)
Abstract The frequency of the use of drugs that act on the epidermal growth factor receptor (EGFR) is increasing, with the consequent onset of cutaneous toxicity, specifically acneiform eruption. The authors extensively review the topic, focusing on describing how these drugs can affect the skin and its appendages, that is, the pathophysiology that encompasses the cutaneous toxicity related to the use of EGFR inhibitors. In addition, it was possible to list the risk factors that may be associated with adverse effects of these drugs. Based on this recent knowledge, the authors expect to aid in the management of patients who are more vulnerable to toxicity, reduce morbidities, and improve the quality of life of patients undergoing treatment with EGFR inhibitors. Other issues related to the toxicity of EGFR inhibitors, such as the clinical aspects of the acneiform eruption grades, and other different types of cutaneous and mucosal reactions, are also included in the article.